Anticoagulation in patients with cardiac manifestations of Chagas disease and cardioembolic ischemic stroke - Monteiro, Jean M.C.; San-Martin, Daniel L.; Silva, Beatriz C.G.; Jesus, Pedro A.P. de; Oliveira, Jamary, Filho (Arquivos de Neuro-Psiquiatria, 2018)
Objectives To describe anticoagulation characteristics in patients with cardiac complications from Chagas disease and compare participants with and without cardioembolic ischemic stroke (CIS).Methods A retrospective cohort of patients with Chagas disease, using anticoagulation, conducted from January 2011 to December 2014.Results Forty-two patients with Chagas disease who were using anticoagulation were studied (age 62.9±12.4 years), 59.5% female and 47.6% with previous CIS, 78.6% with non-valvular atrial fibrillation and 69.7% with dilated cardiomyopathy. Warfarin was used in 78.6% of patients and dabigatran (at different times) in 38%. In the warfarin group, those with CIS had more medical appointments per person-years of follow-up (11.7 vs 7.9), a higher proportion of international normalized ratios within the therapeutic range (57% vs 42% medical appointments, p = 0.025) and an eight times higher frequency of minor bleeding (0.64 vs 0.07 medical appointments).Conclusion Patients with Chagas disease and previous CIS had better control of INR with a higher frequency of minor bleeding.
Keywords: Chagas disease; warfarin; stroke; atrial fibrillation